Clinicopathological Patterns and Predictors of the Functional Restoration of Immunoglobulin G4-Related Kidney Disease: A Chinese Single-Center Cohort Study - Su, Tao; Wang, Hui; Wang, Suxia; Yang, Li (Frontiers in Medicine, 2021)
Background: Immunoglobulin 4-related disease (IgG4-RD) is a systemic and immunoreactivity-based fibro-inflammatory disease. Immunoglobulin 4-related kidney disease (IgG4-RKD) is a frequently overlooked diagnosis. This study aimed to describe IgG4-RKD and examine factors relevant to the outcome of the kidney. Methods: We studied a prospective IgG4-RKD cohort from 2012 to 2020, and follow-up was conducted. Patients with kidney biopsy-proven IgG4-RKD were further analyzed. Results: Of 42 patients with IgG4-RKD, the mean age was 58.5±8.7 years, with a male-to-female ratio of 5:1. The IgG4-RD responder index was 12.2±3.3. A total of 66.7% of patients presented with acute kidney disease (AKD) or AKD superimposed on preceding CKD. Eight (19.0%) patients showed nephrotic-range proteinuria, and nine (21.4%) had high-titer IgG4-autoantibodies, including ANCA and anti-PLA2R. A kidney biopsy was conducted in 40 patients. Thirty-seven (90.0%) patients were diagnosed with IgG4-related tubulointerstitial nephritis, and 19 (47.5%) of these had concurrent glomerular diseases (membranous nephropathy, n=3; crescentic nephritis, n=11; diabetic kidney disease, n=3; both MN and CrGN, n=2). Patients with an accelerated ESR developed significantly worse renal function (R=0.424, P=0.009). Elevated IgG, IgG4, and IgG4/IgG levels were significantly inversely related to the tubulointerstitial acute injury score (TI-AI). A higher IgG4 responder index (R=0.420, P=0.007), lower complement 3 levels (R=−0.484, P=0.002), and eosinophilia (R=0.329, P=0.038) were correlated with a better restoration of renal function at the first month after immunosuppressive treatment. The greatest recovery of renal function during follow-up was determined by the ESR (R=0.411, P=0.020), eosinophil count (R=0.354, P=0.020), and TI-AI score (R=0.36, P=0.028). Conventional immunosuppressive medication and/or rituximab were prescribed, and 83.3% of patients achieved improved kidney function. Kidney re-biopsies confirmed the remission of interstitial inflammation in two patients under immunosuppressive agents. However, the disease relapse rate was as high as 31.0%. Conclusions: We strongly recommend a kidney biopsy in active IgG4-RD, especially when there is proteinuria and renal dysfunction because concurrent glomerular involvement and active interstitial inflammation should be assessed. ESR, eosinophil count and ESR predict reversible renal outcomes-appropriate and timely immunosuppressive therapy help to achieve a better prognosis.